Morphological features of autoimmune gastritis - Ye. A. Losik; L. S. Selivanova; M. Yu. Konkov; T. L. Lapina; A. S. Tertychnyi; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2014)
Aim of investigation. To estimate presence of classical morphological signs of autoimmune gastritis (AIH) in patients with high titer of antiparietal cells antibodies.Material and methods. Overall 15 patients (3 men and 12 women, 28 to 72 years old) have been included in original study. Clinical symptoms in the study group varied and included both severe В12-deficient anemia and normal levels of pepsinogen I, gastrin-17 and cyanocobalamine. In 4 patients Helicobacter pylori infection has been detected. According to guidelines of the Russian Society of Pathologists in all cases multiple biopsies have been taken at esophagogastroduodenoscopy. Biopsy specimens were processed by the standard technique, sections were stained by hematoxyline and eosine.Results. Classical signs of AIH i.e. atrophy of mucosa of body of the stomach and intestinal metaplasia were not revealed. The signs of feeble inflammation in body of the stomach were found in 6 patients. In 4 cases biopsy specimens had no inflammatory or atrophic changes. Pseudo-hypertrophy of parietal cells was the unique morphological feature found out in these cases. At all patients involvement of antral region of the stomach was marked. Atrophic gastritis with intestinal metaplasia was diagnosed in 4 patients. In 3 cases non-metaplastic variant of patchy atrophic gastritis was present, the rest revealed superficial gastritis with signs of activity in 4 cases. No Н. рylori was found out morphologically.Conclusion. In our investigation in patients with AIG no metaplastic atrophic lesions was found in body of the stomach, while metaplastic atrophy had patchy pattern. The pseudo-hypertrophy of parietal cells as well as dilation of main glands lumen can be the earliest and unique sign found in biopsy specimens. Involvement of antral region was revealed in all patients, in 4 cases it has been related to presence of H. pylori infection at the moment of investigation. Thus, the diagnosis of AIG was based mainly on elevated level antiparietal cells antibodies at blood serum test.